Property Issues in Displacement and Conflict Resolution - Wichert, Tim (Refuge: Canada's Journal on Refugees, 1997)
Property plays an important role in thedecisions made by refugees and displacedpersons regarding durable solutionsfor them and their families. Inparticular, it will affect their decisionwhether to return to their homes. Understandingproperty rights in this contextis imperative, especially foragencies involved in post-conflict rehabilitation.This paper sets out the contextby outlining various legal andpractical considerations. It then looks atspecific initiatives in Mozambique,Bosnia and Nicaragua. For a variety ofreasons, there is a move towards "nonformal" resolution of property disputes,in particular the use of alternative disputeresolution mechanisms. These areconsidered, and seven points of commentand conclusion then follow.